ChemInform Abstract: Stereoselective Retentive Domino Transmetalations of Secondary Alkyllithium Compounds to Functionalized Secondary Alkylcopper Reagents. Issue 4 (January 2016) - Moriya, Kohei; Simon, Meike; Mose, Rasmus; Karaghiosoff, Konstantin; Knochel, Paul
Abstract: The title sequence follows the conditions A)—D) where the starting substrates have a defined stereochemistry with a high d.e.